Pre-packaged food products Business to Consumer (B2C) distance selling and information obligations in Italian mass market retailers - Gaetano Liuzzo; Silvia Rolandi; Andrea Serraino; Silvia Piva; Federica Giacometti (Italian Journal of Food Safety, 2019)
The supply and sale of food online are on the rise. The value of e-commerce in Europe has been estimated in 602 billion euros in 2017, 324 million people in the old continent purchase online. In the European area, the Netherlands and Italy are the countries where the e-commerce market grew faster in the last five years. Nevertheless, in Italy the spread of online shopping has reached the 89.9% of the population between 11 and 74 years old. The access to the Internet, as declared by 43 million Italians, it is carried out from fixed or mobile locations. In terms of revenues the food sector recorded a +24% among the different sectors facing one of the higher grows in terms of percentages. The regulatory framework that disciplines the food products distance selling can be traced back to two fundamental pillars: the European legislation on e-commerce on the one side and the food information to consumers on the other side. Under article 14 of the Regulation (EU) No. 1169/2011, the European legislator states that the mandatory information, as indicated in article 9, shall be available to the consumer before the purchase is concluded and when the product is delivered. The study aims at verifying: the level of compliance by Italians MMR with the information regulation about food products distance selling in relation to (a) the fulfillment of the obligation concerning mandatory provisions and (b) the fulfillment of the obligations concerning availability and readability of the information provided. The research has been conducted analyzing the websites of the ten largest Italian MMR and in particular: if the mandatory information were provided, the availability of the information according to the Regulation (EU) 1169/2011; the number of clicks needed to identify the food product in the website and the number of clicks required to obtain all the information. The observation testified a substantial compliance with the information obligations according to the European regulation. Differently, when considering the availability and readability of the information, from the analysis emerged that consumers have to follow a path that is not immediate and intuitive. Conclusions are provided in relation to the presented research.